6x-3=5z-5

Simple and best practice solution for 6x-3=5z-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x-3=5z-5 equation:


Simplifying
6x + -3 = 5z + -5

Reorder the terms:
-3 + 6x = 5z + -5

Reorder the terms:
-3 + 6x = -5 + 5z

Solving
-3 + 6x = -5 + 5z

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3' to each side of the equation.
-3 + 3 + 6x = -5 + 3 + 5z

Combine like terms: -3 + 3 = 0
0 + 6x = -5 + 3 + 5z
6x = -5 + 3 + 5z

Combine like terms: -5 + 3 = -2
6x = -2 + 5z

Divide each side by '6'.
x = -0.3333333333 + 0.8333333333z

Simplifying
x = -0.3333333333 + 0.8333333333z

See similar equations:

| 7x-4x=132 | | -7652+185x=12790 | | x^4-9x^2-3=0 | | 11.9x=3.57 | | 3-x=12+x | | -31/9=2r | | 4x+20=50-6x | | 7(x+2)+7=21 | | k^2-12k+40= | | 9x-4x=280 | | m+10=21 | | p+(-11)=-13 | | -15=n-(-3) | | 6c+30=7.2 | | 0=b+7/2 | | -9+4x=-49 | | 3(x+32)=7x | | 20(x+9)=4(45+5x) | | p-11.9=-10.8 | | 3=9x^2-18x | | 7x+1=7(x+6) | | -587/80=b-10/15/16 | | -33=x-18 | | (7x+5)-(3x-1)= | | n/19=5 | | -2x-5=5x+16 | | -10=x/14 | | (6x+8)-(7x-9)= | | -2x+4=-2(3x+6) | | 1/7k+1/9k=1 | | x/2+x/3=1/3 | | 7-(4x-3)=5-5x |

Equations solver categories